2005
DOI: 10.1111/j.1471-4159.2005.03581.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of endogenous human NPFF2 receptor by neuropeptide FF in SK‐N‐MC neuroblastoma cell line

Abstract: Neuropeptide FF has many functions both in the CNS and periphery. Two G protein-coupled receptors (NPFF1 and NPFF2 receptors) have been identified for neuropeptide FF. The expression analysis of the peptide and receptors, together with pharmacological and physiological data, imply that NPFF2 receptor would be the primary receptor for neuropeptide FF. Here, we report for the first time a cell line endogenously expressing hNPFF2 receptor. These SK-N-MC neuroblastoma cells also express neuropeptide FF. We used th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 64 publications
(148 reference statements)
2
4
0
Order By: Relevance
“…However, the potency of 1DMe is increased by more than 1 order of magnitude in the rat species. ERK activation by NPFF 2 receptors has been demonstrated previously in rat and human cell lines that were shown to endogenously express the receptor (14,37,38). Here we confirm the specificity of this effect by using recombinant cells.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, the potency of 1DMe is increased by more than 1 order of magnitude in the rat species. ERK activation by NPFF 2 receptors has been demonstrated previously in rat and human cell lines that were shown to endogenously express the receptor (14,37,38). Here we confirm the specificity of this effect by using recombinant cells.…”
Section: Discussionsupporting
confidence: 87%
“…The receptor was demonstrated to couple to G i/o heterotrimeric proteins to inhibit adenylyl cyclase (10) and N-type voltagegated calcium channels (11) and activate G protein-regulated inwardly rectifying potassium channels (12), as well as a putative delayed rectifier K ϩ channel (13). It was also shown to activate MAPK pathways (14). However, the mechanisms regulating NPFF 2 receptor signaling and trafficking have not been studied in detail.…”
mentioning
confidence: 99%
“…Our previous study showed that GnIH directly inhibits cAMP production induced by GnRH in the mouse gonadotrope cell line, LβT2 [38]. Interestingly, NPFF also inhibited FSK-stimulated CRE-luciferase activity [41] or inhibited cAMP levels [42]. The present study suggests that amphioxus PQRFa peptides act as inhibitory peptides on the neuroendocrine system of reproduction and their mode of action is similar to those of vertebrate GnIH and NPFF group peptides.…”
Section: Discussionsupporting
confidence: 61%
“…Transcriptional regulation of receptors by their ligands has been shown in various different studies. Exposure of agonists to G protein-coupled receptors frequently results in downregulation of the receptor transcript levels, but receptor upregulation has also been demonstrated (Siegrist et al 1994, Schanstra et al 1998, Froidevaux & Eberle 2002, Ankö & Panula 2006. Inoue et al (1999) found that calcitonin downregulates calcitonin receptor mRNA in mouse bone marrow cells and Dupre et al (2003) report the ligand-induced downregulation of the PAF-R. On the other hand, gene expression of the human somatostatin receptor type I is actively upregulated by somatostatin (Hukovic et al 1999).…”
Section: K9mentioning
confidence: 99%